Tempo escolar estendido: análise do Programa Ensino Integral (PEI) da Secretaria de Estado da Educação de São Paulo (SEE-SP) Gestão Geraldo Alckmin (2011-2017) - Marques, Saray (2018)
This research examines the proposal, curricular structure and functioning of the Integral Education Program (IEP), formulated by the State Education-SP Secretariat, proposed and implemented in the administration of Governor Geraldo Alckmin (2011-2017), so as to to verify to what extent it promotes the integral formation of the student. In addition to the IEP guiding documents and legislation related to full-time education in Brazil, a theoretical reference was sought in the studies conducted by Teixeira (2000, 2004, 2007), Cavaliere (2006, 2010), Chizzotti and Ponce (2013), Dubet (2008), Delors (1996), Gadotti (2009), Gimeno Sacristán (1998, 2000), Guará (2006), Libaneo (2014), Paro (2009), Ponce (2014), Ponce e Rosa and Torres Santomé (2013b). The study was developed as a qualitative research and field research was carried out through interviews with managers and teachers, as well as the application of a questionnaire to 1st, 2nd and 12th grade students, and 3rd years of high school. The analysis of the results considered: the implementation of the Program, the curricular organization and the 360º evaluation, in order to establish a possible relationship between the one proposed by the IEP and its practice. It was observed in this study that, although it is possible to consider that extended school time allows the student to expand opportunities, on the other hand, the preparation of physical spaces, the availability of material and financial resources for the execution of the Program and the participation of school community in its planning and execution still do not correspond to what is proposed in the IEP